AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY: A CASE STUDY OF THE FIRST YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Clara Putri Audia; Fakhri Ras; Afrianto Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The objectives of this research are to find out the level of speaking anxiety experience by the first year students of English Study Program of Universitas Riau and the factors contributing to it. This is mixed-method research; a research combines both quantitative and qualitative paradigms. Using cluster random sampling, 30 students were taken as the sample of this research. The data were collected through questionnaire and semi-structured interview. The questionnaire was adapted from FLCAS (Foreign Language Classroom Anxiety Scale) designed by Horwitz et al (1986). The result of the questionnaire shows that the students’ speaking anxiety is overall in the mildly anxious level. There were six students (20%) in the level of very anxious, seven students (23%) in the level of anxious, 14 students (47%) in the mildly anxious level, one student (3%) in the relaxed level, and two students (7%) in the very relaxed level. It happened because of several factors from either individual or social factors. From individual factors such as fear of making mistake, feeling under pressure dealing with people, and students still lack of English ability. While from the social factors such as afraid of being laugh by other students and afraid of negative evaluation by teachers. Furthermore, to overcome students’ speaking anxiety several recommendations were given such as students need to find out the factors contribute to their speaking anxiety and try to find the best way to cope with their anxiety. Students also need to do more practice in speaking English. In line with that, teacher should create a comfortable situation for a speaking class. It is because such situation will help students to feel more relaxed to express their idea through speaking activity.Key Words: Speaking, Anxiety, Speaking Anxiety